Mild and selective reduction of aldehydes utilising sodium dithionite under flow conditions - Neyt, Nicole C.; Riley, Darren L. (Beilstein Journal of Organic Chemistry, 2018)
We recently reported a novel hybrid batch–flow synthesis of the antipsychotic drug clozapine in which the reduction of a nitroaryl group is described under flow conditions using sodium dithionite. We now report the expansion of this method to include the reduction of aldehydes. The method developed affords yields which are comparable to those under batch conditions, has a reduced reaction time and improved space-time productivity. Furthermore, the approach allows the selective reduction of aldehydes in the presence of ketones and has been demonstrated as a continuous process.
Keywords: aldehyde reduction; flow chemistry; selective reduction; sodium dithionite